DESIGN AND SWIRLING FLOWANALYSIS OF 100-KW MICRO GAS TURBINE COMBUSTION CHAMBER - Garin Santoso, Andriel
Current research on gas turbines focuses on increasing compactness, efficiency and reducing emissions. This has led to the development of micro gas turbines. Micro gas turbines are mainly used in smaller systems which require less power. Research was previously conducted under the same supervision by Cahyanto on the design and analysis of a radial inflow turbine for 100 kW micro gas turbine. This research will build upon the same initial gas turbine design parameters in designing the combustion chamber. In this research, the combustion chamber for a 100-kW micro gas turbine is designed, and the effect of swirling flow is analyzed. The magnitude of swirl is quantified through varying the swirl number of air flowing through the inlet. Simulation is performed through Computational Fluid Dynamics (CFD) using ANSYS Fluent. The non-premixed species model is used to model the combustion process with Natural gas or CH4 as the fuel. Five different swirl numbers including 0; 0.208; 0.449; 0.608; and 0.778 are used in this research. The combustion process is also analyzed with different equivalence ratios in the primary zone from ? = 0.65 to ? = 1.05, and the jet angle of air entering the admission holes is varied between 30°, 60°, and 90°. The results show that increasing the intensity of the swirl results in a larger recirculation zone to be formed directly adjacent to the combustor inlet. A larger recirculation zone can sustain the combustion process more effectively by allowing better mixing between fuel and air. The simulations show that a swirl number of 0.778 is sufficient for this design and produces outlet temperatures similar to the target inlet temperature of the radial-inflow turbine. Meanwhile, it is observed that varying the jet angle of air entering the combustion liner does not significantly affect the combustion process. Finally, for a fixed fuel flow rate, the rate of combustion is increased with decreasing equivalence ratio as more air is readily available for reaction. However, this also results in increased levels of CO and NOx emissions. For this reason, an equivalence ratio of 0.85 is found to be the most optimal for this design.